2019
DOI: 10.1088/1742-6596/1337/1/012005
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical model of massive spinning particle in four-dimensional Minkowski space

Abstract: We propose the model of massive spinning particle traveling in four-dimensional Minkowski space. The equations of motion of the particle follow from the fact that all the classical paths of the particle lie on a cylinder whose position in Minkowski space is determined by the particle's linear momentum and total angular momentum. All the paths on one and the same cylinder are gauge equivalent. The equations of motion are found in implicit form for general time-like paths, and they are non-Lagrangian. The explic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…We have associated the timelike spinning particle trajectories as curves on parabolic cylinders. We have shown that these curves are solutions to the fourth-order differential equation (28). Equations ( 36), (40) determine the particle momentum and total angular momentum in terms of derivatives of trajectory.…”
Section: World Paths On World Sheetsmentioning
confidence: 94%
See 3 more Smart Citations
“…We have associated the timelike spinning particle trajectories as curves on parabolic cylinders. We have shown that these curves are solutions to the fourth-order differential equation (28). Equations ( 36), (40) determine the particle momentum and total angular momentum in terms of derivatives of trajectory.…”
Section: World Paths On World Sheetsmentioning
confidence: 94%
“…Let us now find explicit solution for α and representation for resultant (28). Introduce special notation for combinations of derivatives of curvature and torsion,…”
Section: World Paths On World Sheetsmentioning
confidence: 99%
See 2 more Smart Citations
“…This substructure is of indefinite physical character within a model for fundamental spin; as such, we shall pursue an alternative model. Beyond Clifford algebras, there are models which seek to avoid the 'internal space' common to models of spin: Savasta et al [30,31] associate spin not with Lorentz symmetry but the ( )  SO 4, symmetry present between three-velocities and rates of change of proper time in Minkowski space; Kaparulin et al [32] relate spin to geometric qualities of a particle worldline, also in Minkowski space; and Bühler [33] connects spin to polarisations of a wave in Euclidean three-space via the Lie group ( )  SL 2, . However, none of these models align with our stated goals of directly utilising only the ( )  SO 3, symmetry of real Euclidean three-space.…”
Section: Algebraic Theories In Physicsmentioning
confidence: 99%